PERAN PSIKOLOGI PERKEMBANGAN DALAM PENDIDIKAN ANAK SEKOLAH DASAR - Desnita, Yolly; Afrini, Afrini; Zen, Zelhendri; Desyandri, Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the importance of developmental psychology in the education of elementary school children aged 6–12 years who are at a crucial stage of cognitive, social, and emotional development, so that teachers' understanding of children's developmental characteristics becomes the basis for designing learning strategies. The research method applies a qualitative approach through literature review. The results of the study indicate that developmental psychology helps teachers understand the stages of children's physical, cognitive, and social-emotional development, character formation, and overcome challenges such as the influence of technology and social media, individual differences, fluctuating learning motivation, and difficulties in social adaptation. The conclusion of this study confirms that developmental psychology has an important role in supporting the educational process of elementary school children by understanding and addressing the various developmental challenges they face, thereby creating an environment that supports children's overall growth and allows them to develop optimally in physical, cognitive, social, and emotional aspects.